2009
DOI: 10.1002/j.2050-0416.2009.tb00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid Production in the Brewing of Rice Wine (Sake)

Abstract: The traditional Japanese alcoholic beverage sake is produced by fermentation of rice by Saccharomyces cerevisiae and Aspergillus oryzae. A. oryzae releases ferulic acid, an antioxidant, from steamed rice during the fermentation process. The concentration of ferulic acid increased with time during fermentation and the production rate peaked 9-12 days post inoculation. Analysis of the fermentation cultures of Aspergillus oryzae, by highperformance liquid chromatography (HPLC), revealed that pcoumaric acid induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…This suggests that the conditions of the mash within the 5 days of the main fermentation stage are favourable for FA release, most probably due to the higher fermentation temperature (30°C). These results are similar to the observations of Uno et al 27 , who reported that the levels of FA increased dramatically from 9-12 days post-inoculation, because of a higher fermentation temperature at this stage. The evolution of the 4-VG levels during the fermentation of Chinese rice wine are presented in Fig.…”
Section: Production Of Ferulic Acid and 4-vinylguaiacol During Industsupporting
confidence: 92%
See 2 more Smart Citations
“…This suggests that the conditions of the mash within the 5 days of the main fermentation stage are favourable for FA release, most probably due to the higher fermentation temperature (30°C). These results are similar to the observations of Uno et al 27 , who reported that the levels of FA increased dramatically from 9-12 days post-inoculation, because of a higher fermentation temperature at this stage. The evolution of the 4-VG levels during the fermentation of Chinese rice wine are presented in Fig.…”
Section: Production Of Ferulic Acid and 4-vinylguaiacol During Industsupporting
confidence: 92%
“…Free FA can be released enzymatically from the cell wall polysaccharides of cereals by employing feruloyl esterase. Feruloyl esterase activity has been reported in a Japanese koji used for brewing shochu 12 and sake 27 . Moreover, the existence of different Shochu koji feruloyl esterases has been proposed 11,12 .…”
Section: Effect Of Temperature On Ferulic Acid Release From Rice Floumentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term administration of ferulic acid is reported to induce resistance to beta-amyloid toxicity in the mouse brain [24]. However, the concentration of ferulic acid in commercially available sake is approximately (0.10-6.6 μg/mL; Uno et al [25]). In a mouse model of receptors in the hippocampus, 10% red wine treatment was affected.…”
Section: Hippocampal Mrna Levelmentioning
confidence: 99%
“…In 1967, a study reported the effect of polishing rate of ingredient rice grains on phenolic compounds in sake (20) and Uno et al (21) researched the formation of ferulic acid in the sake brewing process, however, it is not clear how the different levels of phenolic acid in ingredient rice grains affect the levels in sake. Hence, we investigated factors affecting phenolic acid liberation from rice grains in the sake brewing process, especially focusing on the rice koji making process and koji enzymes, using polished rice grains at different polishing ratios.…”
mentioning
confidence: 97%